Customizing the Angular Memory Effect for Scattering Media - Hasan Yılmaz (American Physical Society, 2021)
The memory effect in disordered systems is a key physical phenomenon that has been employed for optical imaging, metrology, and communication through opaque media. Under the conventional memory effect, when the incident beam is tilted slightly, the transmitted pattern tilts in the same direction. However, the “memory” is limited in its angular range and tilt direction. Here, we present a general approach to customize the memory effect by introducing an angular memory operator. Its eigenstates possess perfect correlation for tilt angles and directions that can be arbitrarily chosen separately for the incident and transmitted waves, and can be readily realized with wave front shaping. This work reveals the power of wave front shaping in creating any desired memory for applications of classical and quantum waves in complex systems.